2013
DOI: 10.1080/09523367.2013.765721
|View full text |Cite
|
Sign up to set email alerts
|

Athlete Development, Athlete Rights and Athlete Welfare: A European Union Perspective

Abstract: The issue of athlete 'dual careers' in Two principal rationales exist for the protection of athletes' access to education and vocational training, namely (a) a rights-based discourse in which athletes are seen to be denied access to education and vocational training which are protected for other workers or citizens; and (b) a performance-based discourse in which the athlete's ability to perform in athletic terms is enhancedby virtue of their access to educational opportunities. The paper reviews the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 8 publications
2
48
0
7
Order By: Relevance
“…This is particularly important as many athletes within the current study described situations where they were actively discouraged, and in some cases prevented, from exploring opportunities outside of their chosen sport. Some researchers have suggested that as revenue is often contingent on obtaining international sporting success, coaches and administrators are far more determined to achieve positive results than create well-rounded athletes (Henry, 2013;Murphy, Petitpas, & Brewer, 1996). Therefore, despite the NZAS championing the ideals of holistic athlete development, its' policy of performance-based funding may be severely limiting the likelihood of this actually occurring.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is particularly important as many athletes within the current study described situations where they were actively discouraged, and in some cases prevented, from exploring opportunities outside of their chosen sport. Some researchers have suggested that as revenue is often contingent on obtaining international sporting success, coaches and administrators are far more determined to achieve positive results than create well-rounded athletes (Henry, 2013;Murphy, Petitpas, & Brewer, 1996). Therefore, despite the NZAS championing the ideals of holistic athlete development, its' policy of performance-based funding may be severely limiting the likelihood of this actually occurring.…”
Section: Discussionmentioning
confidence: 98%
“…Rather, some studies have actually suggested that developing one's personal and sporting self simultaneously fosters excellence that would not be possible with just a singular focus (Carless & Douglas, 2012Henry, 2013;Lally, 2007;Miller & Kerr, 2003). Price et al (2010) found that time away from the rigours of competitive sport provided athletes with both mental and physical rejuvenation.…”
Section: Introductionmentioning
confidence: 96%
“…Even though high performance in elite sport exposes student-athletes to great experiences, it requires a vast commitment at the cost of education, work, family, and other interests in life (Crook & Robertson, 1991). Research in higher education (Aries, McCarthy, Salovey, & Banaji, 2004;Henry, 2013) and sport psychology (Kim & Moen, 2002;Lotysz & Short, 2004;Wylleman & Lavallee, 2004) demonstrates that elite athletes compete at the highest levels of athletic performance as a result of a long-term psychological and physical commitment to training and competition. Wylleman and Lavallee (2004) observed that elite athletes do not only strive to reach the top but also remain at the top in elite sport.…”
Section: Dual-career and Retirement Transition 2mentioning
confidence: 97%
“…Algunos factores deportivos también afectan al abandono escolar en los deportistas de éli-te (Aquilina y Henry, 2010). Por ejemplo, la edad de máximo rendimiento (temprana o tardía); las características propias de la competición (calendario y su frecuencia); la economía del deporte (amateur o profesional) junto con los servicios de apoyo prestados por otros agentes (Consejo Superior de Deportes, Comité Olímpicos, Federaciones, Clubes…) determinan las limitaciones inherentes al tipo de deporte que afectan al deportista (Henry, 2013;North y Lavalle, 2004).…”
Section: Introductionunclassified